2018
DOI: 10.1039/c8ra01446a
|View full text |Cite
|
Sign up to set email alerts
|

The A·T(rWC)/A·T(H)/A·T(rH) ↔ A·T*(rwWC)/A·T*(wH)/A·T*(rwH) mutagenic tautomerizationviasequential proton transfer: a QM/QTAIM study

Abstract: We discovered tautomeric wobbling of the classical A·T DNA base pairs. This data evidence, that only a base pair with Watson–Crick architecture can be a building block of the DNA macromolecule as a genetic material, which is able for the evolutionary self-development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 125 publications
0
7
0
Order By: Relevance
“…Thus, in particular, in previous works (Hoogsteen, 1963; Pous et al, 2008; Brovarets' and Hovorun, 2010, 2014b, 2015f; Brovarets', 2013a,b; Alvey et al, 2014; Nikolova et al, 2014; Acosta-Reyes et al, 2015; Poltev et al, 2016; Zhou, 2016; Szabat and Kierzek, 2017; Ye et al, 2017; Brovarets' et al, 2018a,b,c,d,e,f; Brovarets' and Tsiupa, 2019) by the methods of quantum chemistry we have investigated in details the potential (electronic) energy surface of each of the four biologically important A·T DNA base pairs—Watson-Crick A·T(WC), reverse Watson-Crick A·T(rWC), Hoogsteen A·T(H) and reverse Hoogsteen A·T(rH), leading to the novel conformational or tautomeric states of these base pairs. It was theoretically demonstrated that these A·T(WC/rWC/H/rH) base pairs possess unique ability to perform conformationally-tautomeric transition into the planar wobble A * ·T(w), A·TO2*(w), and A·T * (w) base mispairs, non-planar wobble A·T(w WC ), A·T(w rWC ), A·T(w H ), and A·T(w rH ) base mispairs and incorrect A·T * (wWC), A·TO2*(wrWC), A·T * (wH), and A·TO2*(wrH) base mispairs containing mutagenic tautomers of the DNA bases, and also their interconversions between each other through the non-planar transition states via the structural or conformational rearrangements and intramolecular proton transfer along the intermolecular H-bonds.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Thus, in particular, in previous works (Hoogsteen, 1963; Pous et al, 2008; Brovarets' and Hovorun, 2010, 2014b, 2015f; Brovarets', 2013a,b; Alvey et al, 2014; Nikolova et al, 2014; Acosta-Reyes et al, 2015; Poltev et al, 2016; Zhou, 2016; Szabat and Kierzek, 2017; Ye et al, 2017; Brovarets' et al, 2018a,b,c,d,e,f; Brovarets' and Tsiupa, 2019) by the methods of quantum chemistry we have investigated in details the potential (electronic) energy surface of each of the four biologically important A·T DNA base pairs—Watson-Crick A·T(WC), reverse Watson-Crick A·T(rWC), Hoogsteen A·T(H) and reverse Hoogsteen A·T(rH), leading to the novel conformational or tautomeric states of these base pairs. It was theoretically demonstrated that these A·T(WC/rWC/H/rH) base pairs possess unique ability to perform conformationally-tautomeric transition into the planar wobble A * ·T(w), A·TO2*(w), and A·T * (w) base mispairs, non-planar wobble A·T(w WC ), A·T(w rWC ), A·T(w H ), and A·T(w rH ) base mispairs and incorrect A·T * (wWC), A·TO2*(wrWC), A·T * (wH), and A·TO2*(wrH) base mispairs containing mutagenic tautomers of the DNA bases, and also their interconversions between each other through the non-planar transition states via the structural or conformational rearrangements and intramolecular proton transfer along the intermolecular H-bonds.…”
Section: Introductionmentioning
confidence: 90%
“…At this, the so-called Löwdin G * ·C * (WC) base pair with geometry close to Watson-Crick, which is created in such a way, involving mutagenic tautomers of the DNA bases, can acquire similarly to the A·T(WC) base pair different conformations (Brovarets' and Hovorun, 2010, 2015f; Brovarets', 2013a,b; Brovarets' et al, 2018a,b,c,d,e,f; Brovarets' and Tsiupa, 2019)—reverse Löwdin G * ·C * (rWC), Hoogsteen G * ′·C * (H) and reverse Hoogsteen G * ′·C * (rH) (Brovarets', 2013b) (here and below the superscript “ * ” denotes the rare tautomeric form of the DNA base (Glushenkov and Hovorun, 2016) and “′”— trans -orientation of the OH group). This demonstrates quite unexpected role of the Löwdin's tautomerisation for the conformational variety.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results indicated that the non-dissociative transitions occurred via specific intermolecular interaction along the intrinsic reaction coordinate (IRC) (Brovarets' and Pérez-Sánchez, 2017). It showed that the tautomeric transitions for A·T DNA base pairs are non-planar and high-energetic intrapair bases (Brovarets' and Hovorun, 2014a, 2015b,d; Brovarets' et al, 2015, 2018a,b,c,d).…”
Section: Proton Transfer In Nucleobasesmentioning
confidence: 99%
“…The tautomerization products—the A*∙Т(rw WC ), A* N7 ∙Т(rw H ) and A* N7 ∙Т(w H ) pairs—further transform via concerted asynchronous double proton transfer into the energetically favorable wobble A∙T*(rw WC ), A∙T*(rw H ) and A∙T* O2 (w H ) mispairs (symmetry C s ), respectively. Moreover, it was established in our recent papers, that wobble A*∙T(rw WC ) base mispair can also be formed from the reverse A∙T(rWC) base pair [ 20 ], A*·T(wWC) base mispair—from the canonical A∙T(rWC) base pair [ 19 ] and A* N7 ·Т(w H ) base mispair—from the Hoogsteen A∙T(H) base pair [ 20 ].…”
Section: Discussionmentioning
confidence: 99%